Posttraumatic left pleural hematoma complicated by mediastinal hematoma and pneumothorax in a young male: a case report - Głowacki, Jan; Filipowski, Marek; Lewandowski, Roman; Wojtacha, Jacek; Hawranek, Michał; Greiff, Małgorzata; Miszalski-Jamka, Karol; Jackowska, Zuzanna; Rokicki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The authors present a rare case of pleural hematoma complicated by pneumothorax and mediastinal hematoma. The traumatic history was not clear. 3 days after trauma the pain in the chest occurred and that was the reason for coming to the hospital admission room where the chest X-ray was not done. The patient with a suspected heart attack was sent to the Silesian Centre of Heart Diseases, where after the diagnostic procedure the patient was sent to the Thoraco-surgery Hospital for videothoracoscopy.